Agricultural Census 2010 in Latvia - Raubena, Anita (Lithuanian Journal of Statistics, 2011)
The aim of this paper is to describe the organisation of the Agricultural Census 2010 in Latvia, to disclosethe methods of data acquisition used, as well as to present a short analysis of the provisional results of the census. The papersubstantiates the necessity of agricultural censuses and indicates opportunities for the use of information acquired in thecensus. In the research made within the framework of this paper the methods of induction and deduction as well as statisticalanalyses, including grouping, processing and comparing are used. Provisional results of the Agricultural Census 2010 showthat agricultural holdings in Latvia are consolidating – they have became larger and economically more viable: their sownareas are growing as well as the average number of livestock per holding. In 2010 on average per holding there were 33.8 haof land, of which 21.5 ha were utilized agricultural land. The average size of herd per holding growing cattle was 11 cattle, ofwhich 5 were dairy cows.